The cartel party, consensus democracy and democracy without politics - Katz, Richard S. (Politologia, 2018)
Although the age of the mass party as an organizational form is long in the past, the mass party remains a widely accepted normative ideal, closely connected to the idea of party government and to a voters-as-principals-parties-as-agents understanding of democracy. In evolving from mass party, to catch-all party, to cartel party European democracies have also been evolving towards an ‘anti-political’ view of government, along with models of consensus democracy and the regulatory state. This evolution helps to explain the decline in popular connection to political parties. Ironically, the associated causes of this decline are generally regarded as good, notwithstanding that the decline itself is often identified as a crisis. Moreover, analysis of this decline suggests as striking similarity between the consensus model of democracy and the cartel party model of democracy, notwithstanding that the first is often seen as a goal to which democracies should be moving while the second is seen as a threat to democracy itself.